1980
DOI: 10.1126/science.209.4460.1014
|View full text |Cite|
|
Sign up to set email alerts
|

Aeromagnetic and Radio Echo Ice-Sounding Measurements Show Much Greater Area of the Dufek Intrusion, Antarctica

Abstract: A combined aeromagnetic and radio echo ice-sounding survey made in 1978 in Antarctica over the Dufek layered mafic intrusion suggests a minimum area of the intrusion of about 50,000 square kilometers, making it comparable in size with the Bushveld Complex of Africa. Comparisons of the magnetic and subglacial topographic profiles illustrate the usefulness of this combination of methods in studying bedrock geology beneath ice-covered areas. Magnetic anomalies range in peak-to-through amplitude from about 50 nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…lanjy et al, 1991) or a thick pile of Jurassic age Kirkpatrick basalt flows (Behrendt et al, 1991b). A significant component of remanent magnetization, which would be likely for volcanic rocks and some plutonic rocks (Q in the Dufek intrusion ranges from 1.3 to 5; Behrendt et al, 1980) would not produce anomalies characteristic of the present field direction as we observe (Behrendt et al, 1994). Because the Antarctic plate has been essentially stationary for the past 100 million years, Late Cretaceous magnetic granitoids (for example) cannot be ruled out based on magnetization directions; however, we would not expect magnetizations or susceptibilities as high as are required to produce the observed anomalies over the 1 -3-km-thick ice sheet at 1-km flight elevations above the ice.…”
Section: Aeromagnetic and Radar Ice Sounding Surveysupporting
confidence: 41%
“…lanjy et al, 1991) or a thick pile of Jurassic age Kirkpatrick basalt flows (Behrendt et al, 1991b). A significant component of remanent magnetization, which would be likely for volcanic rocks and some plutonic rocks (Q in the Dufek intrusion ranges from 1.3 to 5; Behrendt et al, 1980) would not produce anomalies characteristic of the present field direction as we observe (Behrendt et al, 1994). Because the Antarctic plate has been essentially stationary for the past 100 million years, Late Cretaceous magnetic granitoids (for example) cannot be ruled out based on magnetization directions; however, we would not expect magnetizations or susceptibilities as high as are required to produce the observed anomalies over the 1 -3-km-thick ice sheet at 1-km flight elevations above the ice.…”
Section: Aeromagnetic and Radar Ice Sounding Surveysupporting
confidence: 41%
“…1). The Dufek layered intrusion of the Pensacola Mountains (Antarctica) is thought to form part of the Ferrar magmatic province and was originally proposed to be one of the largest layered mafic intrusions worldwide (Ford 1976, Behrendt et al 1980, 1981, Ford & Himmelberg 1991. However, recent studies have demonstrated it to be considerably smaller than originally thought (Ferris et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…A combined aeromagnetic and radio echo ice-sounding survey indicates a minimum area of over 50,000 km 2 for the intrusion compared with the --•66,000 km 2 for the Bushveld Complex [Behrendt et al, 1974[Behrendt et al, , 1980. A combined aeromagnetic and radio echo ice-sounding survey indicates a minimum area of over 50,000 km 2 for the intrusion compared with the --•66,000 km 2 for the Bushveld Complex [Behrendt et al, 1974[Behrendt et al, , 1980.…”
Section: Tectonic Settingmentioning
confidence: 91%
“…In addition, the presence of large-amplitude magnetic anomalies to the north and east of the surveyed area is suggestive of an even greater extent [Behrendt et al, 1980 Dufek complexes are similar in size and are thus at least an order of magnitude larger than other PGE-bearing mafic layered intrusions (for example, the Stillwater Complex, Montana, United States). The combined thickness of these two sections and the intervening part covered by the Sallee Snowfield is estimated to be 6 to 7 km [Ford, 1970], and the geophysical evidence [Behrendt et al, 1980] suggests that there is another 1.8 to 3.5 km of unexposed basal portion. The lowermost 1.8 km of exposed rocks makes up the Dufek Massif section, and the upper exposed section forms the Forrestal Range.…”
Section: Tectonic Settingmentioning
confidence: 95%